Vulnerabilities in The Procurement of Ordinary Passport Blanks of The Republic of Indonesia: A Systematic Review of Threats to National Nee - Namora, Tondi; Riyanta, Stanislaus (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study aims to analyze vulnerabilities in the procurement of ordinary passport blanks in Indonesia using the Miles and Huberman data analysis method. A qualitative approach is used to identify the factors that lead to a high dependence on a single blank provider, as well as their impact on the smooth procurement process of passports. This study found that uncertainty in the supply of blanks, limited human resource capacity, and potential deviations in the procurement process are the main causes of vulnerability. External factors such as global disruption also exacerbate this situation. The results of the study show the importance of diversifying blank providers to reduce dependence on one party, as well as the need to strengthen a more transparent and efficient procurement system. The study also proposes the digitization of passport services as a strategic step to reduce reliance on physical blanks and improve the efficiency of public services. Overall, this study provides recommendations that can support government policies in improving the resilience and reliability of the public document procurement system in Indonesia, as well as a reference for further research in this field.